The Influence of Students’ Habit of Listening to English Songs on Their Pronunciation Ability - Sovia Kusuma Dewi; Semi Sukarni; Tusino Tusino (Scripta : English Department Journal, 2020)
The objectives of the research to find out whether there is or not positive and significant influence of students’ habit of listening to English songs on their pronunciation ability. The sample of this research was 26 students used purposive sampling. The instrument to take the data was questionnaire and documentation. The technique of analyzing data were descriptive analysis and inferential analysis to answer the statement of the problem and hypothesis. The result of the research showed that the testing r value was lower than r table (0.185< 0.388) and the R square was 0.34. From the computations, it means that Ho was accepted. Therefore, there was positive and gave no significant influence between students’ habit of listening to English songs on their pronunciation ability at of the second semester students of Muhammadiyah University of Purworejo in the academic year oof 2019/2020.